Different faces of Nocardia infection in renal transplant recipients. Issue 3 (March 2016) - Shrestha, Shailendra; Kanellis, John; Korman, Tony; Polkinghorne, Kevan R; Brown, Fiona; Yii, Ming; Kerr, Peter G; Mulley, William
Abstract: Aim: Nocardia infections are an uncommon but important cause of morbidity and mortality in renal transplant recipients. The present study was carried out to determine the spectrum of Nocardia infections in a renal transplant centre in Australia. Methods: A retrospective chart analysis of all renal transplants performed from 2008 to 2014 was conducted to identify cases of culture proven Nocardia infection. The clinical course for each patient with nocardiosis was examined. Results: Four of the 543 renal transplants patients developed Nocardia infection within 2 to 13 months post‐transplant. All patients were judged at high immunological risk of rejection pre‐transplant and had received multiple sessions of plasmaphoeresis and intravenous immunoglobulin before the onset of the infection. Two patients presented with pulmonary nocardiosis and two with cerebral abscesses. One case of pulmonary nocardiosis was complicated by pulmonary aspergillosis and the other by cytomegalovirus pneumonia. All four patients improved with combination antibiotic therapy guided by drug susceptibility testing. At the time of Nocardia infection all four patients were receiving primary prophylaxis with trimethoprim/sulphamethoxazole (TMP/SMX) 160/800 mg, twice weekly. Conclusion: Plasmaphoeresis may be risk factor for Nocardia infection and need further study. Nocardia infection may coexist with other opportunistic infections. Identification of the Nocardia species and drug susceptibility testing is essential in guiding the effective management of patients with Nocardia. Intermittent TMP‐SMX (one double strength tablet, twice a week) appears insufficient to prevent Nocardia infection in renal transplant recipients. Summary at a Glance: This manuscript examines the spectrum of Nocardia infections in a renal transplant centre in Australia. The findings observed in this study provide useful information in the fields of renal transplantation.